MANFAAT TANAMAN SAGU (Metroxylon sp) DALAM PENYEDIAAN PANGAN DAN DALAM PENGENDALIAN KUALITAS LINGKUNGAN - Hariyanto, Bambang (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Sago plants is a source of carbohydrates that can be used as a source of food. WithÃ‚Â the extruder technology, sago can be made noodles. The purpose of this study is toÃ‚Â know the utilization of sago as a provider of food and protecting the environment.Ã‚Â Organoleptic testing sago noodles and wheat noodles to the panelists gave resultsÃ‚Â not significantly different. The noodles of sago have a high resistant starch and usefulÃ‚Â for health. To make use of sago in the manufacture of noodles in the framework ofÃ‚Â implementation of the Gouverment Regulation (Per Pres) No. 22 th 2009 the need forÃ‚Â socialization and support for raw material supplies through sago plantations. WhenÃ‚Â the sago plant is developed it will be beneficial to the absorption of carbon dioxide andmaintain the sago air. Sago palm can produced 20 tonnes karbohidrat / ha. BesidesÃ‚Â sago plants will be able to keep the water around it. Sago leaf has the ability to absorbcarbon dioxide (CO2) emissions by 240 tons CO2/ha/th.